2008
DOI: 10.1007/s11655-008-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress in research on the anti-tumor effect of artesunate

Abstract: It has been found in recent years that Artesunate (Art), a water soluble derivative of arteannuin, mainly previously used for its anti-malarial activity, has some other effects, e.g. it could act as an anti-tumor agent by way of inducing cell apoptosis, antagonizing angiogenesis, reversing immunosuppression of tumor cells, etc. More and more attention is being paid to the anti-tumor effects of Art. Such progress is reviewed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Our data also showed that microvessel density in the bone marrow from 70 patients with MM, a relative large sample size, was significantly higher than that of the control group, confirmed Sezer's conclusions [2]. Some published data showed that ART inhibited in vitro angiogenesis induced by leukemia K562 cells [21] and inhibited blood vessel development in vivo induced by Kaposi's sarcoma, malignant ovarian cancer of mouse models [19,22].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our data also showed that microvessel density in the bone marrow from 70 patients with MM, a relative large sample size, was significantly higher than that of the control group, confirmed Sezer's conclusions [2]. Some published data showed that ART inhibited in vitro angiogenesis induced by leukemia K562 cells [21] and inhibited blood vessel development in vivo induced by Kaposi's sarcoma, malignant ovarian cancer of mouse models [19,22].…”
Section: Discussionsupporting
confidence: 84%
“…ART is a semi-synthetic artemisinin derivative and is more effective than artemisinin. In the past decade, the antitumor activity of ART has been the center of interest as a candidate drug for cancer treatment [19][20][21][22]. Several studies confirmed that ART induced damage of cancer cell DNA, arrested cell cycle, inhibited the proliferation of solid tumor cells and reversed the suppressed immune function related to tumor cells [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, tumor therapy by traditional Chinese herb is becoming more and more attractive (He et al, 2008;Youns et al, 2009;Chen et al, 2010). We therefore attempted to examine the effects of triptolide and artesunate on pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, artesunate is considered for the treatment of malignancy [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Its efficacy in malignancy may at least in part result from its ability to induce tumor cell apoptosis [13,14,23,25,26,28,29,30,31]. The proapoptotic effect has been attributed in part to mitochondria [23,25,29].…”
Section: Introductionmentioning
confidence: 99%